Corrections to “Converging Technologies for Health Prediction and Intrusion Detection in Internet of Healthcare Things With Matrix-Valued Neural Coordinated Federated Intelligence” - Sarah A. Alzakari; Arindam Sarkar; Mohammad Zubair Khan; Amel Ali Alhussan (IEEE Access)
Presents corrections to the paper, (Corrections to “Converging Technologies for Health Prediction and Intrusion Detection in Internet of Healthcare Things With Matrix-Valued Neural Coordinated Federated Intelligence”).